A confirmative clinimetric analysis of the 36-item Family Assessment Device. (19th May 2018) - Timmerby, Nina; Cosci, Fiammetta; Watson, Maggie; Csillag, Claudio; Schmitt, Florence; Steck, Barbara; Bech, Per; Thastum, Mikael
Abstract: Background: The Family Assessment Device (FAD) is a 60-item questionnaire widely used to evaluate self-reported family functioning. However, the factor structure as well as the number of items has been questioned. A shorter and more user-friendly version of the original FAD-scale, the 36-item FAD, has therefore previously been proposed, based on findings in a nonclinical population of adults. Aims: We aimed in this study to evaluate the brief 36-item version of the FAD in a clinical population. Methods: Data from a European multinational study, examining factors associated with levels of family functioning in adult cancer patients' families, were used. Both healthy and ill parents completed the 60-item version FAD. The psychometric analyses conducted were Principal Component Analysis and Mokken-analysis. Results: A total of 564 participants were included. Based on the psychometric analysis we confirmed that the 36-item version of the FAD has robust psychometric properties and can be used in clinical populations. Conclusions: The present analysis confirmed that the 36-item version of the FAD (18 items assessing 'well-being' and 18 items assessing 'dysfunctional' family function) is a brief scale where the summed total score is a valid measure of the dimensions of family functioning. This shorter version of the FAD is, in accordance with the concept of 'measurement-based care', an easy to use scale that could be considered when the aim is to evaluate self-reported family functioning.